2006
DOI: 10.1089/aid.2006.22.529
|View full text |Cite
|
Sign up to set email alerts
|

SIV-Associated Myocarditis: Viral and Cellular Correlates of Inflammation Severity

Abstract: Myocarditis is a common finding in HIV-infected people. Cardiac inflammatory lesions and functional abnormalities similar to those documented in HIV infection are frequently seen in SIV infection of rhesus monkeys, suggesting a shared disease mechanism. A retrospective analysis of cardiac tissue collected at necropsy was performed to assess correlates of myocardial inflammation in SIV-infected rhesus monkeys. Intramyocardial SIV-infected cells were identified in 7 of 21 hearts from SIV-infected animals, with v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…43 In these studies, there were increased numbers of CD163 + macrophages in SIV-infected animals with normal, uninflammed heart tissue, and fewer CD163 + macrophages in SIV-infected animals with active or borderline myocarditis.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…43 In these studies, there were increased numbers of CD163 + macrophages in SIV-infected animals with normal, uninflammed heart tissue, and fewer CD163 + macrophages in SIV-infected animals with active or borderline myocarditis.…”
Section: Discussionmentioning
confidence: 67%
“…42 Yearley et al found 1-4 SIV-infected macrophages/mm 2 in hearts of 7 of 21 animals. 43 These authors used an antibody against SIV-nef that detects latent and productively infected macrophages. We found SIV-p28 and SIV-RNA-positive macrophages in brains and lymph nodes of the animals in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, tissue sections were heated and rehydrated, incubated in 1% hydrogen peroxide in methanol (CD4) or 3% hydrogen peroxidase in phosphate-buffered saline (PBS) (HLA-DR, Ki67, and CD3), and subjected to antigen retrieval procedures, including microwaving in 0.01 M citrate buffer (Dako, Carpinteria, CA) (Ki67 and CD3) or heating under pressure in 1 mM EDTA-0.05% Tween (CD4), as previously described (11). Nonspecific staining was blocked with Dako protein block, and sections were incubated overnight at 4°C with primary antibodies to Ki67, HLA-DR, CD3 (Dako), or CD4 (Vector Laboratories, Burlingame, CA) or appropriate isotype-matched irrelevant MAb controls, followed by incubation with biotinylated secondary antibody (Dako).…”
Section: Animals and Immunizationsmentioning
confidence: 99%
“…However, it cannot be excluded that this finding may be an indication of general lymphatic activation during the course of SIV infection (Yearley et al, 2006). The percentages of the other minor CV findings (hydropericardium, dilatative cardiomyopathy, myocardial fibrosis, and myocardial hypertrophy) were previously not defined as being SIV-specific and correspond to findings which can regularly be found in healthy rhesus macaques, regarding their extent and severity (Chamanza et al, 2006).…”
Section: Inflammatory Infiltrates and Other Minor Findingsmentioning
confidence: 86%
“…Altered arterial walls and cardiomyocytes were immunohistochemically negative for SIV antigen. Myocarditis seems to be unrelated to the infection of cardiomyocytes with SIV (Yearley et al, 2006), but it may be associated with the accumulation of inflammatory cells in heart tissue in the context of the general activation of the immune system and regional microbial translocation (Pandrea et al, 2015). The disparity in the extent and intensity of IHC staining with the two different antibodies is likely attributable to the fact that the antibodies are directed against different proteins.…”
Section: Immunohistochemical Detection Of Siv Antigen In Cardiovasculmentioning
confidence: 99%